2010
DOI: 10.1038/eye.2010.61
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal bevacizumab for type 1 idiopathic macular telangiectasia

Abstract: Purpose To evaluate the effect of intravitreal bevacizumab injection for treating type 1 idiopathic macular telangiectasia (IMT). Methods Retrospective case series of five eyes of five male patients with type 1 IMT that were treated with 2-3 injections of intravitreal bevacizumab. Best-corrected visual acuity, foveal thickness obtained by optical coherence tomography, and fluorescein angiography (FA) were monitored over a period of up to 12 months. Results The average follow-up period was 17.0 months (range, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…Gamulescu et al [1] reported a case of type 1 IMT in whom a single administration of IVB was remarkably effective. In contrast, Takayama et al [3] and Matsumoto and Yuzawa [4] reported that IVB had limited efficacy for type 1 IMT; the courses of their studies resemble our case. These were all small case series, and further investigations are necessary to determine the efficacy of IVB for this type of aneurysm.…”
Section: Discussioncontrasting
confidence: 62%
“…Gamulescu et al [1] reported a case of type 1 IMT in whom a single administration of IVB was remarkably effective. In contrast, Takayama et al [3] and Matsumoto and Yuzawa [4] reported that IVB had limited efficacy for type 1 IMT; the courses of their studies resemble our case. These were all small case series, and further investigations are necessary to determine the efficacy of IVB for this type of aneurysm.…”
Section: Discussioncontrasting
confidence: 62%
“…Recently, studies examining the use of intravitreal injections of bevacizumab as a treatment for this condition have found it to be inconsistent in its outcomes [7, 1518]. Only a few cases have been reported on the use intravitreal injections of triamcinolone acetonide with promising results [5].…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature provides conflicting reports regarding the benefit of intravitreal anti-VEGF drugs in controlling macular edema in Coats disease, clinical experience has been that these agents induce a short-lived response that is often inadequate to prevent disease progression after a single treatment. 44,[60][61][62][63] We lack evidence that young patients have a structurally immature retina or that physiologic revascularization occurs in the adult retina. However, VEGF-A is a critical molecule with multiple bioactivities: processes which involve VEGF-A are listed in the Table 4.…”
Section: Role Of Anti-vascular Endothelial Growth Factor Drugsmentioning
confidence: 97%